Air Gun Impactor—A Novel Model of Graded White Matter Spinal Cord Injury in Rodents - Marcol, Wiesław; Ślusarczyk, Wojciech; Gzik, Marek; Larysz-Brysz, Magdalena; Bobrowski, Michał; Grynkiewicz-Bylina, Beata; Rosicka, Paulina; Kalita, Katarzyna; Węglarz, Władysław; Barski, Jarosław J.; Kotulska, Katarzyna; Łabuzek, Krzysztof; Lewin-Kowalik, Joanna (Journal of Reconstructive Microsurgery, 2012)
Understanding mechanisms of spinal cord injury and repair requires a reliable experimental model. We have developed a new device that produces a partial damage of spinal cord white matter by means of a precisely adjusted stream of air applied under high pressure. This procedure is less invasive than standard contusion or compression models and does not require surgical removal of vertebral bones. We investigated the effects of spinal cord injury made with our device in 29 adult rats, applying different experimental parameters. The rats were divided into three groups in respect to the applied force of the blast wave. Functional outcome and histopathological effects of the injury were analyzed during 12-week follow-up. The lesions were also examined by means of magnetic resonance imaging (MRI) scans. The weakest stimulus produced transient hindlimb paresis with no cyst visible in spinal cord MRI scans, whereas the strongest was associated with permanent neurological deficit accompanied by pathological changes resembling posttraumatic syringomyelia. Obtained data revealed that our apparatus provided a spinal cord injury animal model with structural changes very similar to that present in patients after moderate spinal cord trauma.
Keywords: spinal cord injury; animal model; trauma; syringomyelia